Women Language Used by the Main Character in the “Black Widow” Movie: Sociolinguistic Study - Amanda Putri Syarifudin; Hero Gunawan (Budapest International Research and Critics University, 2022)
This research aims to identify the features of women language that are found and the dominant features of the women language in the utterances of the main character in the